Innovative educational congklak media in prasiaga scout activities: stimulating critical thinking and social skills in early childhood - Nuraisyah; Kurnia, Rika; Herman; Herlina; Bactiar, Yusri; Hajerah (Program Pascasarjana Universitas Negeri Yogyakarta, 2024)
Critical thinking skills are essential competencies that need to be developed from an early age, as they play a vital role in the processes of analysis, problem-solving, and decision-making. Study aimed to develop and examine the effectiveness of the innovative traditional game